Transformative Approach to Developing a Sustainable Interprofessional Education Program - Tilicia Mayo-Gamble; Jane Nester; Paula Tillman; Sandhya Lohani; Padmini Shankar; Pamela Mahan (Georgia Southern University, 2023)
Background: The ability to offer and sustain interprofessional collaboration and education (IPE) in an academic setting could potentially serve as a training model for other academic institutions to implement programs that will increase the number of practice-ready, culturally competent healthcare professionals. We designed, implemented, and evaluated an Area Health Education Center (AHEC) Scholars Program to train culturally competent interdisciplinary students to provide quality, patient-centered healthcare in rural and underserved communities post-graduation. Methods: Two cohorts of students (Cohort 1, n = 15, Cohort 2, n = 14) were recruited into a two-year longitudinal program with 80 hours of didactic learning and 40 community-based training. Core areas included: 1) interprofessional education and practice; 2) social determinants of health; 3) cultural competency; 4) behavioral health integration; 5) practice transformation; and 6) emerging health topics. Following completion of each content area, students participated in synchronous debriefing sessions and provided feedback via surveys. Wilcoxon ranks test assessed differences in pre- and post-scores in intention, perceived knowledge, and perceived skills for each content area. Results: Students' intention, perceived knowledge, and perceived skills significantly changed from pre- to post-program in all core areas (p < .05). The greatest change from pre- to post-program was perceived knowledge in interprofessional education (D = 1.75). Interactive activities were most useful for keeping students engaged. Conclusion: The program resulted in significant changes for participating students in their intention, perceived knowledge, and perceived skills. Implications for this training program include guidance for academic institutions and AHECs to integrate IPE training.